Analisis Uji Kelayakan Buku Dasar Listrik dan Elektronika Kelas X Sekolah Menegah Kejuruan - Ravi Novriansyah; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2020)
he position of a textbook is very important in the world of education and is a source for teachers and students. The development of the world of books in Indonesia, which has continued rapidly until now, has provided many choices for educational institutions, teachers, and students to get the various books they want. Selection of books that are appropriate, easy to understand and learn, contain content that is in accordance with the applicable curriculum, and students will support the achievement of learning objectives. This research aims to determine the feasibility and utilization of the Basic Electricity and Electronics book. The research use a descriptive method. The subject of this research is the book Basic Electricity and Electronics Class X Mediatama publisher by Dewi Wahyuningsih. Respondents of research are students of class X TITL and teachersof Basic Electrical and Electronics subjects. The data was taken using a questionnaire created using google form. Therefore the Covid-19 so that the distribution of the questionnaire was carried out online. Data analysis was percentage technique. The results of research was obtained that the teacher responses to the content and presentation feasibility include the good criteria, while the students' responses to the use of book include the good criteria.